Cost Effectiveness of Contracting Out Vaccination Services in Two Districts of Sindh, Pakistan - Shiraz Shaikh; Kashif Shafique (Asia Pacific Journal of Health Management)
Objectives: To determine the differences in costs of providing vaccination services in contracted and non-contracted primary care facilities, and to analyze their effectiveness using vaccination volume data